PSYCHOTROPIC DRUGS – I - MalliK, Utpal (SCHOOL SCIENCE, 2013)
Drug-taking is an age-old practice almost in every society. But in this article, our chief concern is the weakness among young people and students for the addictive drugs. Here, we shall try to acquaint ourselves with the various natural and synthetic drugs, and then, with the nature and extent of drug use, the social basis of drug dependency and the contemporary youth culture vis-a-vis drug taking. Contemporary drug use is somehow related to the loss of faith in reason and emphasis on emotion. Such qualities like self-control, planning and patience are grossly devalued. Past and future have become meaningless to many; the reason for living is sought within present experience, here and now. The motivational patterns behind drug addiction, however, vary from drug to drug and person to person. It is not enough to know that our young friends become drug addicts. Perhaps it is more important to know why they become so. Weakness towards psychotropic drugs is neither born in a social vacuum nor can it be explained in terms of a group or individual viewed in isolation from the rest of the society.